2015
DOI: 10.5812/ircmj.19373
|View full text |Cite
|
Sign up to set email alerts
|

Treatment Following Intoxication With Lethal Dose of Paraquat: A Case Report and Review of Literature

Abstract: Introduction:Paraquat is a widely used nitrogen-based herbicide which is lethal and causes multi-organ failure by accumulation in cells, which subsequently leads to death.Case Presentation:The present case report introduced a 25-year-old male with nausea, vomiting, and severe substernal burning sensation after incidentally ingestion of a large amount of paraquat. The treatment of the patient with antioxidants (N-acetylcysteine and vitamin E) and hemodialysis started immediately after arriving to the hospital.C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…28 Nausea, vomiting, and a severe substernal burning sensation are indicated after accidental poisoning caused by ingesting approximately 100 ml of PQ (60% solution) concentration. 29 Nausea, vomiting, discomfort, and neutropenia were observed in a 15-year-old girl, who ingested a small quantity of wine full of PQ. 30 Similarly, 10 symptoms including cough, diarrhea, eye irritation, headache, nausea, rhinitis, throat irritation, breath- ing trouble, unusual tiredness, and wheezing were found to be significantly elevated after PQ exposure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…28 Nausea, vomiting, and a severe substernal burning sensation are indicated after accidental poisoning caused by ingesting approximately 100 ml of PQ (60% solution) concentration. 29 Nausea, vomiting, discomfort, and neutropenia were observed in a 15-year-old girl, who ingested a small quantity of wine full of PQ. 30 Similarly, 10 symptoms including cough, diarrhea, eye irritation, headache, nausea, rhinitis, throat irritation, breath- ing trouble, unusual tiredness, and wheezing were found to be significantly elevated after PQ exposure.…”
Section: Discussionmentioning
confidence: 99%
“…49 In addition, epilepsy or convulsion was investigated in clinical case reports and studies. 28,29,50 Therefore, PQ-induced neurotoxicity is a matter of concern and should be prevented or treated in intoxicated patients. These findings indicated that PQ poisoning patients should be followed up for a long time after discharge from a hospital.…”
Section: Discussionmentioning
confidence: 99%
“…It is highly effective at killing plants, but is also known to be highly toxic to humans. Ingestion of paraquat causes organ failure and subsequently death, and poisoning with this herbicide results in the highest rate of mortality of all pesticides (Davarpanah et al, 2015). In South Korea, paraquat was commonly used as a method of suicide prior to its prohibition (Myung et al, 2015).…”
Section: Herbicide Banningmentioning
confidence: 99%
“…Paraquat also induces the multi‐organ toxicity with necrotic damages to the lung, liver, kidneys and heart (Davarpanah et al . 2015). Since paraquat is corrosive, mild poisoning can irritate the upper gastrointestinal tract and respiratory tissue resulting in abdominal pain, nausea, vomiting, diarrhoea and acute respiratory distress.…”
Section: Introductionmentioning
confidence: 99%